Immune Response to Mycobacterium tuberculosis: A Narrative Review - de Martino, Maurizio; Lodi, Lorenzo; Galli, Luisa; Chiappini, Elena (Frontiers in Pediatrics, 2019)
The encounter between Mycobacterium tuberculosis (Mtb) and the host leads to a complex and multifaceted immune response possibly resulting in latent infection, tubercular disease or to the complete clearance of the pathogen. Macrophages and CD4+ T lymphocytes, together with granuloma formation, are traditionally considered the pillars of immune defense against Mtb and their role stands out clearly. However, there is no component of the immune system that does not take part in the response to this pathogen. On the other side, Mtb displays a complex artillery of immune-escaping mechanisms capable of responding in an equally varied manner. In addition, the role of each cellular line has become discussed and uncertain further than ever before. Each defense mechanism is based on a subtle balance that, if altered, can lean to one side to favor Mtb proliferation, resulting in disease progression and on the other to the host tissue damage by the immune system itself. Through a brief and complete overview of the role of each cell type involved in the Mtb response, we aimed to highlight the main literature reviews and the most relevant studies in order to facilitate the approach to such a complex and changeable topic. In conclusion, this narrative mini-review summarizes the various immunologic mechanisms which modulate the individual ability to fight Mtb infection taking in account the major host and pathogen determinants in the susceptibility to tuberculosis.